Ionizing radiation-induced foci persistence screen to discover enhancers of accelerated senescence - Labay, Edwardine (Int J High Throughput Screen, 2011)
Much like replicative senescence, the irreversible cell-cycle arrest induced by eroded telomeres, accelerated senescence occurs when replicative cells suffer irreparable DNA double-strand breaks (DSBs). Along with apoptosis and necrosis, senescence is a desirable outcome in cancer treatment with ionizing radiation (IR) or chemotherapy. In both normal and cancer cells, DSBs promote the assembly of IR-induced foci (IRIF), domains of modified chromatin that serve a key role in DNA damage signaling. IRIF persistence is a critical determinant of accelerated senescence, making drugs that promote persistent IRIF an attractive strategy to sensitize cancer to genotoxic therapy. As an IRIF reporter, we have expressed an inducible green fluorescent protein (GFP) fusion to the IRIF-binding domain (IBD) of 53BP1 (GFP-IBD) in the breast cancer cell line MCF7. Within minutes of exposure to IR, the GFP-IBD relocalizes to form fluorescent nuclear foci, which disperse within several hours. A pair of high-content screening assays for IRIF formation and persistence were established in multiwell plates based on imaging and quantifying GFP-IBD foci per Hoechst-stained MCF7 nucleus at 2 hours and 24 hours. Using the ataxia telangiectasia-mutated inhibitor CGK733 to block IRIF formation and the topoisomerase II inhibitor etoposide to prevent IRIF resolution, we obtained a Z′ >0.8 both for IRIF formation at 2 hours and IRIF persistence at 24 hours. Screening the diverse drugs and natural products in the National Cancer Institute Developmental Therapeutics Program Approved Oncology Drugs Set, the National Institutes of Health Clinical Collection, and the MicroSource Spectrum Collection yielded multiple hits that significantly delayed IRIF resolution. Secondary screening suggested some of these otherwise nontoxic drugs also enhance accelerated senescence, indicating strong potential for their repurposing as radiation sensitizers to improve the efficacy of cancer therapy.